The conditions of the water sector in Poland - Lis, P. (Економічний вісник Донбасу, 2016)
The aim of this article was to identify and assess the conditions of the water sector in Poland. The author has distinguished global and direct conditions of the water sector. What has been emphasised among the global conditions was a different structure and dynamics of water needs in developing countries and in developed countries. It has been assumed that the global Sustainable Development Goals formulated in 2015 focus primarily on the issue of fresh water availability rather than the issue of water quality. Nonetheless, the latter aspect is reflected in the European Union water policy and in state regulations. According to the author, adapting water service enterprises to more and more complicated regulations, requiring increasingly large financial resources, will constitute a major threat for the development of the exceptionally fragmented water sector in Poland. This sector is made up of water service enterprises, the majority of which administer small networks of distribution. This threat will be strengthened by a decreasing - in the long term - demand for fresh water, given rather small water resources in Poland. Additionally, it has been assessed that the pace of the growth of water network infrastructure was faster than the pace of an increase in the access to the public water distribution network. The author has also highlighted the danger for the water sector stemming from a scattered structure of residential developments, which came as a result of poor land management. Apart from this, the author believes that it is crucial to improve the operational efficiency of the water sector, in particular by optimising possessed property, improving water quality and customer services, as well as conforming to the EU regulations in terms of risk assessment.